Understanding Business Behavior of the Chinese Indonesian: a Study Using Hofstede’s Cultural Framework - Suharnomo, Suharnomo (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2017)
The success of the Chinese Indonesian in doing business in Indonesia is an interesting sub-ject yet it is seldom discussed within the cultural dimensions perspective. This study aimed to explore how the work value within Chinese Indonesian cultural dimension. The dimensions of the Chinese Indonesian culture might become important information to be understood in order to do and deal business with this ethnic group. This study applied Value Survey Module 1982 of Hofstede. The research was conducted in Semarang, with total respondents of 152 who work as employers and workers. The findings of this study proved that Chinese people still hold values and ideas of their ancestral culture that affect their work value as shown by the scores of the cultural dimensions of Hofstede’s. Overall, the findings of this study indicated that the Chi-nese Indonesian is characterized by having high power distance, strong uncertainty avoidance, collectivism, and masculine. Since the present research only studied Chinese Indonesian, future research is suggested to expand and add more comparisons other ethnic groups and observe whether each ethnic group also have distinctive characteristics